The history of language learning and teaching in Britain - McLelland, Nicola (Taylor & Francis, 2018)
This article provides an overview, based on the most recent research available, of the history of language learning and teaching (HoLLT) in Britain. After an overview of the state of research, we consider which languages have been learnt, why, and how that has changed; the role of teachers and tests in determining what was taught; changes in how languages have been taught (and why); and the emergence of the modern infrastructure of language teaching policy and practice. After this general survey, we conclude with a more in-depth discussion of the contribution of one key figure, Walter Rippmann, in the period of 1895 to ca. 1920, a time of professionalization of language teaching and of efforts towards innovation and change, which set the agenda for many of the major developments of the twentieth century, including a call for scientifically-based language teaching and a greater emphasis on the spoken language.